Comparison of male and female HIV seroprevalence rates from a coal mining community and mobile clinic in Mpumalanga, South Africa - Hurkchand, Hitesh Pravinchundra (My University, 2009)
Comparison of HIV seroprevalence between males and females at clinic and community level in Mpumalanga South Africa. Background: Two cross-sectional surveys were conducted in Embalenhle community (February 2002) and Dunusa community mobile clinics (November 2001), to establish prevalence of HIV and STIs (Chlamydia trachomatis and Neisseria gonorrhea). Methods: Multiple logistic regression models were fitted to the combined data from the two sites, to identify factors associated with HIV prevalence and also to check whether the effects were consistent over the two sites. Results: HIV Prevalence was 33.5% (30.2%vs.35.9% in males and females respectively, p=0.124) at community site and 34.8% at clinic site (22.8%vs.47.4% in males and females respectively, p=0.001). The models show a significant site by sex interaction i.e. the effect of sex differs in the 2 sites (p=0.036). After adjusting for agegroup and Neisseria gonorrhea, predicted probabilities from the logistic regression model shows that the sex difference is much greater in community mobile clinics (23%vs.44.1% in males and females respectively) than at the community site (29.9%vs.34.9% in males and females respectively). After adjusting for site and Neisseria gonorrhea, the model showed an agegroup by sex interaction (p<0.001). Predicted probabilities show a difference, where HIV in males is higher than in females; in males in the 25-34 year age group from 18-24 years (36.3 vs 18.2 % respectively), while in females the prevalence is very similar in the 18-24 year and 25-34 year age groups. There were no interactions between Neisseria gonorrhea and other variables. Conclusions: The different HIV–age distribution for males and females are consistent with the results of previous studies. We found that the sex difference in prevalence was much smaller at the community level than at the clinic level. The traditional interpretation of national antenatal surveillance data assumes a fairly large difference in male and female seroprevalence (a ratio of 7:10 is used in extrapolating results of the South African National antenatal seroprevalence survey to males). These results suggest that more work is needed in checking that assumption.
Keywords: HIV seroprevalence; Mpumalanga; South Africa